Alterations in Red Blood Cell Functionality Induced by an Indole Scaffold Containing a Y-Iminodiketo Moiety: Potential Antiproliferative Conditions. (29th August 2016) - Scala, Angela; Ficarra, Silvana; Russo, Annamaria; Barreca, Davide; Giunta, Elena; Galtieri, Antonio; Grassi, Giovanni; Tellone, Ester
Abstract : We have recently proposed a new erythrocyte-based model of study to predict the antiproliferative effects of selected heterocyclic scaffolds. Starting from the metabolic similarity between erythrocytes and cancer cells, we have demonstrated how the metabolic derangement induced by an indolone-based compound (DPIT) could be related to its antiproliferative effects. In order to prove the validity of our biochemical approach, in the present study the effects on erythrocyte functionality of its chemical precursor (PID), whose synthesis we reported, were investigated. The influence of the tested compound on band 3 protein (B3), oxidative state, ATP efflux, caspase 3, metabolism, intracellular pH, and Ca 2+ homeostasis has been evaluated. PID crosses the membrane localizing into the cytosol, increases anion exchange, induces direct caspase activation, shifts the erythrocytes towards an oxidative state, and releases less ATP than in normal conditions. Analysis of phosphatidylserine externalization shows that PID slightly induces apoptosis. Our findings indicate that, due to its unique features, erythrocyte responses to exogenous molecular stimuli can be fruitfully correlated at structurally more complex cells, such as cancer cells. Overall, our work indicates that erythrocyte is a powerful study tool to elucidate the biochemical/biological effects of selected heterocycles opening considerable perspectives in the field of drug discovery.